REGIONAL ECONOMIC POTENTIAL IN INCREASING LOCAL OWN-SOURCE REVENUE OF THE PROPOSED MALAMOI REGENCY EXPANSION FROM SORONG REGENCY - Sipora Mince Krimadi; James Modouw; Lazarus Ramandei (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the regional economic potential in increasing Local Own-Source Revenue (PAD) in the proposed expansion of Malamoi Regency from Sorong Regency. A mixed-methods descriptive approach was employed, incorporating qualitative descriptive analysis, Location Quotient (LQ), and sectoral contribution analysis. The findings reveal that the Malamoi region has six main economic potentials: agriculture, livestock, forestry, fisheries and marine, mining, and tourism. Based on LQ analysis, the broad agricultural sector is a base sector (LQ = 1.42 > 1) with potential as the primary economic driver, while the mining and tourism sectors are classified as non-base sectors (LQ < 1). In terms of contribution, the mining sector contributes the most (15.68%), the broad agricultural sector contributes moderately (9.57%), and tourism contributes minimally (0.33%). The study concludes that the economic potential of Malamoi can support PAD growth and strengthen regional fiscal independence when managed optimally with adequate infrastructure support.